2010
DOI: 10.1007/s13197-010-0062-9
|View full text |Cite
|
Sign up to set email alerts
|

Retort pouch processing of Chettinad style goat meat curry — a heritage meat product

Abstract: Chettinad style goat meat curry, a heritage meat product, was thermal processed in retort pouches having 4 layer confi gurations. Physical properties of retort pouches indicated that they are suitable for processing. Pouches fi lled with 150 g of goat meat and 100 g of curry medium were retorted to a F O value of 12.1 min. Retort cooked products were tested for sterility and quality characteristics. Retorting decreased the product pH, thiobarbituric acid reactive substances and shear force values. Retort proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 20 publications
8
22
0
1
Order By: Relevance
“…This is in conformity with report of Rajkumar et al (2010) who stored retort processed chevon up to 10 months. The release of moisture in the gravy during heat denaturation of proteins might have contributed for sampling error during storage studies.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This is in conformity with report of Rajkumar et al (2010) who stored retort processed chevon up to 10 months. The release of moisture in the gravy during heat denaturation of proteins might have contributed for sampling error during storage studies.…”
Section: Resultssupporting
confidence: 93%
“…Similar trend was also observed during storage by Prince Devadason et al (2010) in retort processed buffalo meat block and Rajkumar et al (2010) in retort processed Chettinad goat meat .This might be due to degradation of proteins and liberation of free amino acids.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The sensory evaluation of the ready-to-eat poultry egg keema was done on the basis of organoleptic characteristics to indicate its definite maturation and improvement during storage and it was observed that the samples thermally processed at 120°C for 20 minutes were acceptable in all respects. Similar results were interpreted during the chemical, microbial and sensory analysis of canned meat based mutton and beef curry Madhwaraj [14], Rajkumar et al [15] evaluated the appearance, color, flavor, juiciness, texture and overall acceptability of Chettinad goat meat curry showing scores of 8.0 to 8.4 on a 9-point hedonic scale after thermal treatment.…”
Section: Effect Of Thermal Processing On Ready-to-eat Poultry Egg Keemasupporting
confidence: 54%
“…Rajkumar et al [15] determined total viable, anaerobic, coliform, staphylococcal, streptococcal, clostridial and yeast and mold counts of Chettinad goat meat curry retorted to an F 0 value of 12.1 minutes and showed that the product was commercially sterile. Statistical analysis showed that the calculated value of F due to treatments (time, temperature and days) is greater than the tabulated value at 5% probability level, concluding the significant effect of treatments on the microbial count of samples ( Figure 6).…”
Section: Effect Of Thermal Processing On Microbiological Characteristmentioning
confidence: 99%